2013
DOI: 10.1002/jor.22364
|View full text |Cite
|
Sign up to set email alerts
|

Hip abduction can prevent posterior edge loading of hip replacements

Abstract: Edge loading causes clinical problems for hard-on-hard hip replacements, and edge loading wear scars are present on the majority of retrieved components. We asked the question: are the lines of action of hip joint muscles such that edge loading can occur in a well-designed, well-positioned acetabular cup? A musculoskeletal model, based on cadaveric lower limb geometry, was used to calculate for each muscle, in every position within the complete range of motion, whether its contraction would safely pull the fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 31 publications
1
50
1
Order By: Relevance
“…Although the cup position has the largest effect on edge loading, kinematics can still affect the risk of edge loading after surgery. Whereas previous research showed that abduction can prevent posterior edge loading in large flexion angles, this study suggests that during gait, antero‐superior edge loading can be prevented by decreasing hip extension during terminal double support.…”
Section: Discussioncontrasting
confidence: 94%
See 3 more Smart Citations
“…Although the cup position has the largest effect on edge loading, kinematics can still affect the risk of edge loading after surgery. Whereas previous research showed that abduction can prevent posterior edge loading in large flexion angles, this study suggests that during gait, antero‐superior edge loading can be prevented by decreasing hip extension during terminal double support.…”
Section: Discussioncontrasting
confidence: 94%
“…Cup positions representing the edges of Lewinnek's safe zone were used, as well as coverage angles representative for commonly used prosthesis cups. 7,29 For all eight conditions, HCF-edge angles at the timing of the first and second peak hip contact force in the reference simulation were reported. Also the minimal HCF-edge angle during the entire stance phase and the corresponding magnitude and timing of the hip contact force were reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hip, tibiofemoral, patellofemoral and ankle joint kinematic models were all based on anatomical considerations (see Supplementary material). Muscular lever arms were computed using a muscular geometry derived from that proposed by Klein Horsman et al [24] and adjusted by van Arkel et al [25]. This geometry consisted of 129 muscular lines of action representing 38 muscles, divided into 55 units with up to 6 bundles.…”
Section: Musculoskeletal Modelmentioning
confidence: 99%